2021
DOI: 10.1111/tbed.14207
|View full text |Cite
|
Sign up to set email alerts
|

A cost‐benefit analysis of foot and mouth disease control program for smallholder cattle farmers in Cambodia

Abstract: The Cambodian government is attempting to mobilise government, donor and private sector funding to implement a coordinated FMD vaccination program (FMDVP). A necessary first step is to convince the farmers of the benefits of participating in and potentially financially supporting this program. Information was collected from 300 farmers in order to estimate the on-farm benefits and costs of their participation in an FMDVP.Implementing a successful vaccination program is difficult, and farmers understand from pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…No samples from cattle originating from Thailand were collected in our study, which was similar to our previous study [ 6 ] and indicated that reported livestock transboundary movements from Thailand to Vietnam and China via Lao PDR [ 49 , 50 , 51 ] are not used to supplement the local trade. The movement visualisations showed that some provinces, including Bolikamxai, Luang Namtha, Xiangkhouang, and Vientiane prefecture, sourced animals from longer distances compared to other provinces.…”
Section: Discussionsupporting
confidence: 87%
“…No samples from cattle originating from Thailand were collected in our study, which was similar to our previous study [ 6 ] and indicated that reported livestock transboundary movements from Thailand to Vietnam and China via Lao PDR [ 49 , 50 , 51 ] are not used to supplement the local trade. The movement visualisations showed that some provinces, including Bolikamxai, Luang Namtha, Xiangkhouang, and Vientiane prefecture, sourced animals from longer distances compared to other provinces.…”
Section: Discussionsupporting
confidence: 87%
“…Introducing information into short training programmes for VAHWs and smallholder farmers on the importance of economic losses due to FMD and benefits from disease prevention is considered necessary to improve future vaccination uptake and disease control programmes in Cambodia. The conclusion from the 2013 study confirmed that it is worthwhile for farmers to participate in the full‐fee bi‐annual FMD vaccination programme if there are average annual outbreaks with a morbidity rate of approximately 30% and two major outbreaks with morbidity rate above 50% in the ensuing 5 years (Sieng, Patrick, Walkden‐Brown, & Sar, 2022). This is consistent with conclusions from the 2015 survey that also suggested that improved training of VAHWs could ensure they remain important in supporting the under‐resourced national veterinary services (MacPhillamy et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Improvement of FMD control requires the cooperation of villagers, VAHWs and village leaders in disease reporting, with either improved funding of government vaccination services and/or development of a private FMD vaccination service. Both strategies should be accompanied by training programmes for farmers on disease transmission and the importance of biosecurity and vaccination, including information on the cost‐benefits of treatment versus full fee bi‐annual FMD vaccination (Sieng, Patrick, Walkden‐Brown, & Sar, 2022; Sieng, Patrick, Windsor, et al., 2022). These initiatives are urgently required in Cambodia if the substantial increase in future FMD vaccination rates currently needed is to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kappes et al (2023), the presence of animal diseases in production impacts markets, which is evident through the implementation of trade bans and restrictions. It is imperative to restrict the movement of animals and humans across farms since they can serve as potential disease vectors to mitigate the spread of diseases (Sieng et al, 2022). Due to dealer activity's absence, farmers have encountered challenges in conducting livestock trade.…”
Section: Introductionmentioning
confidence: 99%